2009
DOI: 10.3389/neuro.09.013.2009
|View full text |Cite
|
Sign up to set email alerts
|

Posterior midline and ventral parietal activity is associated with retrieval success and encoding failure

Abstract: The ventral part of lateral posterior parietal cortex (VPC) and the posterior midline region (PMR), including the posterior cingulate cortex and precuneus, tend to show deactivation during demanding cognitive tasks, and have been associated with the default mode of the brain. Interestingly, PMR and VPC activity has been associated with successful episodic retrieval but also with unsuccessful episodic encoding. However, the differential contributions of PMR and VPC to retrieval vs. encoding has never been demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
141
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 54 publications
16
141
3
Order By: Relevance
“…Furthermore, the activation of the left precuneus decreased with time for both Meaningful and Form-only words. The precuneus is known to be a part of the episodic/autobiographical memory network (Cavanna & Trimble, 2006), and is more active at retrieval than encoding (Daselaar et al, 2009;Huijbers et al, 2012). Thus the activation of this area is likely to reflect episodic memory retrieval, consistent with the idea that the episodic nature of the recognised novel words declined with time.…”
Section: Memory Representations Of Newly Acquired Wordssupporting
confidence: 50%
“…Furthermore, the activation of the left precuneus decreased with time for both Meaningful and Form-only words. The precuneus is known to be a part of the episodic/autobiographical memory network (Cavanna & Trimble, 2006), and is more active at retrieval than encoding (Daselaar et al, 2009;Huijbers et al, 2012). Thus the activation of this area is likely to reflect episodic memory retrieval, consistent with the idea that the episodic nature of the recognised novel words declined with time.…”
Section: Memory Representations Of Newly Acquired Wordssupporting
confidence: 50%
“…Instead, in older adults, larger right MFG volume was positively correlated with greater activity in the right parietal cortex, midline regions, and right caudate. Previous studies have reported positive associations between posterior midline cortical activity and improved retrieval success (Daselaar et al, 2009) and between posterior midline cortical and caudate activity during declarative retrieval (Burianova et al, 2010). Therefore, these activations may reflect a change in the retrieval network associated with right MFG volume with age.…”
Section: Age-related Changes In Right More Than Left Mfg Volumementioning
confidence: 88%
“…However, there were some trends in the data linking PHC microstructure to total recall in the FCSRT. Recent evidence suggests that the posteromedial cortex extending into the posterior cingulate cortex is critical for strategic memory processes related to successful encoding/retrieval and meta-memory (Daselaar et al, 2009). Thus, it may be the case that the PHC contributes to strategic aspects of memory not directly assessed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Episodic memory is supported by networks spanning frontal, temporal, and parietal lobes (Fletcher and Henson, 2001;Simons and Spiers, 2003;Cabeza et al, 2008). The various interconnections are presumed to enable distinct aspects of memory (Aggleton and Brown, 2006;Wilding and Herron, 2006;Daselaar et al, 2009). Whereas the differential effects of gray matter lesions have been extensively studied (Ranganath, 2010), less is known about the interconnecting fiber tracts.…”
Section: Introductionmentioning
confidence: 99%